THE FUNDAMENTALS OF DEVELOPING LEARNERS’ ORAL SKILLS THROUGH STORYTELLING (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article discusses about storytelling which brings language learning alive and creates a participatory and immersive experience that allows Young Learners to enjoy hearing the language in a dynamic, sometimes stylistic and entertaining way. Participation using key vocabulary and phrases can create an awareness of rhythm and structure. This atmosphere of play and creative expression creates an appetite for more similar experiences. Students who have enjoyed storytelling in class often ask for more stories and also feel motivated and encouraged to create and tell, act out or illustrate their own stories in a variety of ways